DESIGN DAN PEMBUATAN PEMODELAN ENERGI HYBRID BERBASIS ENERGI MATAHARI DAN ENERGI HYDRO DENGAN BACK FLOW WATER SYSTEM - Heri Suripto; Saiful Anwar; Amri Abdulah (Jurnal Rekayasa Mesin, 2023)
Hybrid power is a combination of two or more alternative energy sources to produce high-efficiency electrical energy under different load conditions. Hybrid energy research has been carried out through previous research, including combining solar and wind, solar and biomass, hydro, thermal, wind, solar and solar with thermoelectric generators. This study designs a hybrid power plant model based on solar and hydroelectricity with a water circulation system. Water falling from the upper reservoir into the lower reservoir is returned to the upper reservoir using an electric pump, and this study is a development of previous research related to alternative hydropower. The method used in this study is the Pahl and Beitz method, including design sketches, material selection, fabrication, and testing phases. The solar cell frame design produced by the Pahl and Beitz process is 100 cm high and 65 cm wide, and the module type used is a 3-piece polycrystalline module. The average power output produced by the 3 solar panels to the cells was 19.76 watts. The test produced 850 watts of total hybrid power, 600 watts DC from solar, and 250 watts DC from hydro.